Burnout of Parent Who Have Children with Cerebral Palsy Disability in Bandung City - Enkeu Agiati; Enung Huripah (Asian Social Work Journal, 2019)
Burnout refers to feelings of physical, emotional and mental exhaustion of parents who have children with cerebral palsy disabilities. The purpose of the research was to examine: 1) Characteristics of the subject, 2) Feelings of physical fatigue, 3) Feelings of emotional fatigue, and 4) Feelings of mental fatigue. The method used was descriptive qualitative method. The data sources used are primary and secondary data sources. The technique of determining the informants used was purposive. Data collection techniques used were in-depth interviews, participatory observation, and documentation study. The criteria for checking data validity used credibility test, transferability test, dependability test, conformbility test with the technique of extending participation, observation persistence, and triangulation. Data analysis techniques used qualitative data analysis techniques. The results showed that parents who have cerebral palsy children experience burnout characterized by feelings of physical, emotional and mental fatigue. However, feelings of physical and emotional exhaustion can still be overcome properly, only the feeling of mental fatigue cannot be overcome.